Time Discretization Schemes for an Integro-Differential Equation of Parabolic Type (Journal of Computational Mathematics, 1994)
In this paper a new approach for time discretization of an integro-differential equation of parabolic type is proposed. The methods are based on the backward-Euler and Crank-Nicolson Schemes but the memory and computational requirements are greatly reduced without assuming more regularities on the solution u.